Gambaran Tingkat Pengetahuan Tentang Mitigasi Bencana Tanah Longsor pada Remaja di Desa Jeruk Selo Boyolali - Dwi Cahyo Pribadi Putro; Siti Fatmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Landslides are the movement of slope-forming materials in the form of rocks, debris, soil, or mixed materials that move down or out of the slope. Lack of public knowledge on handling emergency response, mitigation, and disaster preparedness can cause a lot of losses. This problem has been recorded since 2020, 572 landslides have been found with landslide-prone locations in Indonesia totaling 6,664 areas. Anticipation of landslides can be overcome by providing education on disaster risk management by providing landslide disaster mitigation. The purpose of this study was to describe the level of knowledge about landslide disaster mitigation among adolescents in Dayu hamlet, Jeruk village, Selo sub-district, Boyolali district. This study uses quantitative descriptive with the number of respondents as many as 50 teenagers who were selected based on total sampling technique. The analytical method used is univariate analysis. The study showed that the level of knowledge of adolescents regarding landslide disaster mitigation was found to be 88% (44 respondents) with good knowledge. The level of knowledge of adolescents related to landslide disaster mitigation in Dayu hamlet, Jeruk village, Selo sub-district, Boyolali district, was mostly well-informed.